2022
DOI: 10.1017/s2040174422000137
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs from early childhood and adolescence are associated with pre-diabetes at 18 years of age in women from the PMNS cohort

Abstract: With type 2 diabetes presenting at younger ages, there is a growing need to identify biomarkers of future glucose intolerance. A high (20%) prevalence of glucose intolerance at 18 years was seen in women from the Pune Maternal Nutrition Study (PMNS) birth cohort. We investigated the potential of circulating microRNAs in risk stratification for future pre-diabetes in these women. Here, we provide preliminary longitudinal analyses of circulating microRNAs in normal glucose tolerant (NGT@18y, N = 10) and glucose … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…have been associated with lipid accumulation and adipocyte differentiation in low-birth-weight adult humans 32 , and with increased subcutaneous adipose tissue in ammation 33 , respectively. In an earlier study we found that hsa-miR-212-3p is associated with increased risk of glucose intolerance in young adult PMNS female participants 34 . Fetal miRNAs hsa-miR-204-3p (FC=9.87 in adipose group) and hsa-miR-342-3p (FC=-0.098) have been shown to promote adipogenic differentiation of mesenchymal stem cells 35,36 and hsa-miR-15a (FC= -0.912) to regulate intramuscular adipogenesis 37 .…”
Section: Discussionmentioning
confidence: 85%
“…have been associated with lipid accumulation and adipocyte differentiation in low-birth-weight adult humans 32 , and with increased subcutaneous adipose tissue in ammation 33 , respectively. In an earlier study we found that hsa-miR-212-3p is associated with increased risk of glucose intolerance in young adult PMNS female participants 34 . Fetal miRNAs hsa-miR-204-3p (FC=9.87 in adipose group) and hsa-miR-342-3p (FC=-0.098) have been shown to promote adipogenic differentiation of mesenchymal stem cells 35,36 and hsa-miR-15a (FC= -0.912) to regulate intramuscular adipogenesis 37 .…”
Section: Discussionmentioning
confidence: 85%
“…Maternal miRNAs hsa-miR-483-3p (FC= 3.99 in adipose group) and hsa-miR-212-3p (FC=0.282 in adipose group) have been associated with lipid accumulation and adipocyte differentiation in low-birth-weight adult humans 32 , and with increased subcutaneous adipose tissue inflammation 33 , respectively. In an earlier study we found that hsa-miR-212-3p is associated with increased risk of glucose intolerance in young adult PMNS female participants 34 . Fetal miRNAs hsa-miR-204-3p (FC=9.87 in adipose group) and hsa-miR-342-3p (FC=-0.098) have been shown to promote adipogenic differentiation of mesenchymal stem cells 35,36 and hsa-miR-15a (FC= −0.912) to regulate intramuscular adipogenesis 37 .…”
Section: Discussionmentioning
confidence: 85%
“…Instead, we chose to study hsa-mir-30e-3p, a member of the miRNA-30 family, which is highly expressed in beta-cells, according to the same database. Interestingly, members of the miRNA-30 family have been reported to affect beta-cell insulin production, apoptosis and transdifferentiation to alpha-cells, and to function as biomarkers for pre-diabetes ( 30 32 ). We observed that blocking the binding of hsa-mir-30e-3p to ADA1 mRNA resulted in reduced intracellular adenosine levels, both at control conditions and in cells exposed to palmitate + high glucose ( Figure 8A ).…”
Section: Resultsmentioning
confidence: 99%